Synergistic effect of Huyang Yangkun Formula and embryonic stem cells on 4-vinylcyclohexene diepoxide induced premature ovarian insufficiency in mice - Meifang Li; Li Xie; Yang Li; Jian Liu; Guangning Nie; Hongyan Yang (BMC, 2020)
Abstract Background Huyang Yangkun Formula (HYYKF) was developed based on theory of traditional Chinese medicine as well as clinical experience and used to improve ovarian function of premature ovarian insufficiency (POI) patients. Transplantation of embryonic stem cells (ESCs) has great potential in improving POI, and studies have confirmed that traditional Chinese medicine promoted the treatment effect of ESCs. In the present study, we compared the effect of combining HYYKF and ESCs, single HYYKF treatment and single ESCs intervention on POI mice to explore the effect of combination of HYYKF and ESCs in improving ovarian function. Methods C57BL/6 mice were used to create a POI model by 15-day intraperitoneal injection of 160 mg/kg of 4-vinylcyclonhexene diepoxide (VCD) and then treated with HYYKF, ESCs transplantation and combination of ESCs and HYYKF. When the treatments were finished, estrus cycle, ovarian follicle counting, serum sex hormone level, and expression of key nodes in the transforming growth factor beta/transforming growth factor beta-activated kinase 1 (TGF-β/TAK1) signaling pathway were determined. Results Combination therapy brought down the abnormal estrus cycle rate to 5.26%, significantly lower than that of HYYKF or ESCs alone (30%, 25%, respectively). The numbers of follicles at all levels were increased significantly in the combination ESCs with HYYKF group (P < 0.05), especially that of antral follicles (P < 0.01), which was not increased significantly when HYYKF or ESCs was single used. The level of anti-Mullerian hormone (AMH) was more significantly increased in the combination ESCs with HYYKF group (P < 0.01) than that of HYYKF or ESCs alone (both P < 0.05). The expression of the key nodes TGF-β1, TAK1, JNK, Smad4 and FSHR in the TGF-β/TAK1 pathway were obviously affected in the SCHY group. Conclusion Both HYYKF and ESCs improve the ovarian function of POI induced by VCD, and a combination of HYYKF and ESCs has the advantage that they work together to promote follicles developing probably by inhibiting expression of the TGF-β1/TAK1 pathway.